Compositional Dependence of Structural Properties of Prepared Pb𝑥S1−𝑥 Alloys and Films - M. F. A. Alias; A. A. J. Al-Douri; E. M. N. Al-Fawadi; A. A. Alnajjar (Advances in Condensed Matter Physics)
Results of a study of Pb𝑥S1−𝑥 alloys and films with various Pb content have been reported and discussed. Films of Pb𝑥S1−𝑥 of thickness 1.5 μm have been deposited on glass substrates by flash thermal evaporation method at room temperature, under vacuum at constant deposition rate. These films were annealed under vacuum around 10−6 Torr at different temperatures up to 523 K. The composition of the elements in Pb𝑥S1−𝑥 alloys was determined by standard surfaces techniques such as atomic absorption spectroscopy (AAS) and X-ray fluorescence (XRF), and the results were found of high accuracy and in very good agreement with the theoretical values. The structure for alloys and films is determined by using X-ray diffraction. This measurement reveals that the structure is polycrystalline with cubic structure and there are strong peaks at the direction (200) and (111). The effect of heat treatment on the crystalline orientation, relative intensity, and grain size of Pb𝑥S1−𝑥 films is presented.